نماذج من دراسات تقويمية لكتب تعليم اللغة العربية في ماليزيا ودول جنوب شرق آسيا - Chik, Abdul Rahman (2015)
An evaluation study on Arabic textbooks in Malaysia and Southeast Asia. Samples were chosen from various countries. The study found varieties in result ranging from 60%-85% in fulfilling the international standard in writing textbooks specially for second language learners.